2012
DOI: 10.1128/iai.00411-12
|View full text |Cite
|
Sign up to set email alerts
|

Trichinella spiralis Secreted Enzymes Regulate Nucleotide-Induced Mast Cell Activation and Release of Mouse Mast Cell Protease 1

Abstract: Extracellular nucleotides are important triggers of innate immunity, acting on a wide variety of cells via signaling through purinergic receptors. Mucosal mast cells contribute to expulsion of a number of gastrointestinal nematode parasites, and mouse mast cell protease 1 has been shown to have a critical role in clearance of Trichinella spiralis from the intestinal tract. We show here that adenosine, ADP, ATP, UDP, and UTP all stimulate calcium mobilization in bone marrow-derived mast cells with a mucosal phe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Anthony et al (2007) explained that many of effector cells are acti�ated in response to most helminth infections including mast cells. Mucosal mast cells contribute to expulsion of a number of gastrointestinal nematode parasites (Afferson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthony et al (2007) explained that many of effector cells are acti�ated in response to most helminth infections including mast cells. Mucosal mast cells contribute to expulsion of a number of gastrointestinal nematode parasites (Afferson et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, little information is a�ailable describing the effects of A. galli infection on the mucosal defense regarding mast cells response of small jejunal of laying hens. Reference to mucosal mast cells mediate Trichinella spiralis, the nematode resides within enterocytes of the jejunum, expulsion from the intestine of mice has been reported (Ierna et al, 2005;Suzuki et al, 2008;Afferson et al, 2012); howe�er, De-yuan et al (2003) reported that the mucosal mast cells in jejunum of chickens infected with A. galli were increased with no significantly difference but a remarkable decrease of mast cells in the thymic medulla. Thus, the aim of the current study was to in�estigate the effects of A. galli infection on the mucosal defense based on mucosal mast cells response in jejunal of laying hens.…”
Section: Introductionmentioning
confidence: 99%
“…During the enteral phase of trichinellosis, a huge amount of nucleotides are released from damaged tissue. As these free nucleotides stimulate the immune system, T. spiralis worms start to secrete a range of nucleotide‐metabolizing enzymes to decrease the released nucleotides and promote an anti‐inflammatory environment . Interestingly, some recent evidences indicate that recruited mast cells participate in controlling the inflammatory status by enhancing the tissue remodelling process after injury.…”
Section: Discussionmentioning
confidence: 99%
“…T. spiralis‐ secreted molecules have also been shown to selectively modulate the secretion profiles of activated mast cells while T. spiralis muscle larval antigens were demonstrated to induce the release of histamine but inhibit β‐hexosaminidase in mast cells . T. spiralis‐ secreted enzymes were also shown to inhibit mouse mast cell protease 1 .…”
Section: Mast Cells As Therapeutic Targets For Helminth Therapymentioning
confidence: 99%